2016
DOI: 10.1111/bjd.14568
|View full text |Cite
|
Sign up to set email alerts
|

Development of stratum corneum chymotrypsin-like protease activity and natural moisturizing factors from birth to 4 weeks of age compared with adults

Abstract: Conflicts of interest disclosure: None to declare. What's already known about this topic? From birth the acidification and hydration of the infant stratum corneum to adult levels suggests transitory mechanisms underlying differentiation and desquamation. What does this study add? Superficial chymotrypsin-like protease activity and natural moisturising factors (NMF) increase from birth to 4 weeks of age and differ to adults. Impaired barrier function at birth is accompanied by elevated protease activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…Similarly, Chittock et al . reported low NMF in the skin of 115 neonates at birth, with a significant increase in NMF by 4 weeks of age . Low NMF in infant skin at birth is in keeping with reports in variations between neonatal and adult rat skin.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, Chittock et al . reported low NMF in the skin of 115 neonates at birth, with a significant increase in NMF by 4 weeks of age . Low NMF in infant skin at birth is in keeping with reports in variations between neonatal and adult rat skin.…”
Section: Discussionsupporting
confidence: 84%
“…30 Similarly, Chittock et al reported low NMF in the skin of 115 neonates at birth, with a significant increase in NMF by 4 weeks of age. 31 Low NMF in infant skin at birth is in keeping with reports in variations between neonatal and adult rat skin. Scott and Harding reported that during late fetal development filaggrin accumulates throughout the entire thickness of rat SC and immediately after birth filaggrin proteolysis occurs in the outer SC.…”
Section: Discussionsupporting
confidence: 84%
“…Defects in claudins 1, 4 and 8 have also been associated with the development of atopic dermatitis 47 . Disruption of the skin barrier involves defects in the entire keratinocyte terminal differentiation program via dysregulation of multiple EDC genes on human chromosome region 1q21 8 , reduced expression of epithelial tight junction proteins 9 , increased transepidermal water loss (TEWL) 10, 11 , and reduction in epidermal natural moisturizing factors 12 . The impaired skin barrier function in AD also involves altered lipid profiles, including shortening of carbon chain length of stratum corneum lipids (ceramides and free fatty acids), an event that exhibits strong correlations with TEWL and occurs independently of filaggrin mutations 1316 .…”
Section: Barrier Defects In Type 2 Diseasesmentioning
confidence: 99%
“…An important aspect of newborn skin physiology is addressed by Chittock et al . in this issue of the BJD .…”
mentioning
confidence: 99%
“…In parallel, a critical parameter for the SC water‐handling properties is the amount of natural moisturizing factors (NMF), which includes breakdown products of filaggrin decomposition in the SC . In this issue of the BJD , Chittock et al . have evaluated the surface activity of kallikrein‐7 (KLK‐7), an important desquamation enzyme, and the amount of NMF in superficially removed layers of neonatal SC (from birth to the first month of life).…”
mentioning
confidence: 99%